2019
DOI: 10.3390/nano9040549
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Synthesis of Nanopyramidal-Like VO2 Films by an Oxygen-Assisted Etching Growth Method with Significantly Enhanced Field Emission Properties

Abstract: The present investigation reported on a novel oxygen-assisted etching growth method that can directly transform wafer-scale plain VO2 thin films into pyramidal-like VO2 nanostructures with highly improved field-emission properties. The oxygen applied during annealing played a key role in the formation of the special pyramidal-like structures by introducing thin oxygen-rich transition layers on the top surfaces of the VO2 crystals. An etching related growth and transformation mechanism for the synthesis of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…For the N1s spectrum, a binding energy of 398.8 eV, corresponding to the pyridinic-type N in carbon layer [60], was found, indicating the formation of N-doped carbon structure in the V-CF. Moreover, the fitted curves for the V2p spectrum (Figure 2e) indicated that there were two kinds of vanadium valence states with binding energies of 517.4 eV and 516.0 eV, respectively, which can be assigned to the dominant pentavalent vanadium bonds in V 2 O 5 and small amount of V 4+ defect in the sample [61][62][63][64]. For the O 1s spectrum (Figure 2g), three individual peaks, centered at 530.3, 532.3, and 534.1 eV, were found from the fitted XPS curves, which can be attributed to the binding energies of [65], V-OH [66], and C-O [67], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the N1s spectrum, a binding energy of 398.8 eV, corresponding to the pyridinic-type N in carbon layer [60], was found, indicating the formation of N-doped carbon structure in the V-CF. Moreover, the fitted curves for the V2p spectrum (Figure 2e) indicated that there were two kinds of vanadium valence states with binding energies of 517.4 eV and 516.0 eV, respectively, which can be assigned to the dominant pentavalent vanadium bonds in V 2 O 5 and small amount of V 4+ defect in the sample [61][62][63][64]. For the O 1s spectrum (Figure 2g), three individual peaks, centered at 530.3, 532.3, and 534.1 eV, were found from the fitted XPS curves, which can be attributed to the binding energies of [65], V-OH [66], and C-O [67], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Pyramidal VO 2 NS with a novel oxygen-assisted growth method are provided which can highly improve the field emission-properties. In this method the plain planar VO 2 is transformed to the nano-pyramidal surface which is applicable in temperature-regulated field emission devices [40]. Here, the array of VO 2 -based pyramidal NS is a good candidate for proposing an AR-ML-NS.…”
Section: Introductionmentioning
confidence: 99%